ANALISIS PENGARUH BIAYA OPERASIONAL, VOLUME PEMBIAYAAN MURABAHAH DAN BAGI HASIL DPK TERHADAP MARGIN PEMBIAYAAN MURABAHAH STUDI KASUS PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2010-2014 - Raisa Rossalina; Raja Adri Satriawan Surya; Mudrika Alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study was to examine the Effect of Operating Costs, Murabahah Financing Volume and DPK Sharing towards Murabahah Financing Margin Case Study of Islamic Banks in Indonesia 2010-2014. The population in this study include Islamic Banks in Indonesia 2010-2014. The samples were selected by purposive sampling method. The data used in this research is secondary data. Data collection method used is the method of documentation. The analytical method used in this research is multiple linear regression analysis. Based on the data collected and testing has been done on the problem by using the method of regression analysis, it can be concluded: 1) From the results of hypothesis testing, it was found that there is significant influence of Operating Cost to Murabahah Financing Margin in Islamic Banks. 2) From the results of hypothesis testing, it was found that there is significant influence of Murabahah Financing Volume to Murabahah Financing Margin in Islamic Banks. 3) From the results of hypothesis testing, it was found that there is significant influence of DPK Sharing to Murabahah Financing Margin in Islamic Banks.Keywords: Operating Costs, Murabahah Financing Volume, DPK Sharing and Murabahah Financing Margin